India spotlight on population: a demographic outline - Petrov, Victor (Moscow, 1985)
Today more than one-sixth of mankind lives in India, a country that has the second largest population in the world The rates of its population growth which increased after independence, are higher than the average rates for mankind as a whole. In the future the share of India's inhabitants in the population of our planet will become even greater.
Keywords: India-Population